Relación entre prácticas parentales y ajuste psicológico de adolescentes escolarizados. - González-Gutiérrez, Orlando; Navarro Obeid, Jorge; Ortiz Restrepo, Lilibeth; Alarcón-Vásquez, Yolima; Ascanio Castro, Claudia; Trejos-Herrera, Ana María (Archivos Venezolanos de Farmacología y Terapéutica, 2019)
Objective: The purpose was to determine the relationship between Parental Practices and Psychological Adjustment in adolescents enrolled in school. Methods: 142 adolescent students participated. The Parental Practices for Adolescents Scale [PP-A] was used, and for the Psychological Adjustment, and The Youth Self-Report [YSR]. Results: Although a low correlation was found between the variables studied, however, the results denote good parental practices. The Parental Practices of both parents tended to associate negatively with the Psychological Adjustment were Communication, Behavior Control and Autonomy. The maternal Behavior Control was not correlated with Internalized Problems; however, Communication and Behavioral Control of the mother were more significant in relation to Externalized Behavior Problems, and Autonomy, for Internalized Problems. Conclusions: The Parental Practices were considered as favoring the Psychological Adjustment of the evaluated adolescents, particularly, the maternal Communication and the Autonomy promoted by both parents. On the other hand, maternal Imposition and Paternal Psychological Control were better associated with internalized and externalized behavioral problems.